4CPS-227 Evaluation of adherence to inhaled medications in chronic obstructive pulmonary disease. (March 2019) - Hachemi, D; Bagur, N; Knight, M; Roux, C; Richard, H; Dubois, F
Abstract : Background: Chronic obstructive pulmonary disease (COPD) treatment consists mainly of inhaled medications. The evolution of this illness is linked with good compliance. Purpose: The aim of the study was to assess patients' compliance and their ability to use the inhaled medical devices. Material and methods: A prospective, observational, monocentric study was conducted in a university hospital for 2 months. Included patients were treated by inhaled devices for a COPD. A compliance survey (Girerd's questionnaire 1 ) was proposed to them during their hospitalisation. Patients were classified in three groups: fully observant (score equal to 6); poorly observant (score equal to 4 or 5); and non-observant (score inferior to 3). The evaluation of their ability to use the inhaled medical devices is realised, based on national health insurance recommendations. These recommendations stand on the three common steps to inhaled treatment intake: expiration, drug inspiration and holding breath for 10 s. Patients were divided into groups according to the number of accomplished steps. The mean number of steps was collected. Results: Forty-five patients were included in the study. The mean age was 73 years' old and, on average, each patient has two inhaled medical devices. Out of these 45 patients, 16% were considered fully observant, 40% poorly observant and 44% non-observant. The mean compliance score was 3.5 out of 6. Aptitude testing showed that 13%, 16% and 53% of patients, respectively, accomplished 3, 2 and 1 step out of 3, whereas 18% of them respected none. The mean number of steps during inhaled treatment intake was 1.2 out of 3. Conclusion: This study stresses a limitation in compliance in COPD patients with inhaled treatments. Indeed, we can observe a high level of non-observant patients and a majority of them not respecting the necessary steps for the good use of inhalators. This misuse is also confirmed by a limited mean number of accomplished steps during inhalation. These results may suggest that a clinical pharmacist's intervention towards COPD patients using inhaled medication could improve their adherence. References and/or acknowledgements: 1. Girerd, et al. Évaluation de l'observance du traitement anti-hypertenseur par un questionnaire: mise au point et utilisation dans un service spécialisé. Presse médicale. 2001. No conflict of interest.